SUBSTANTIATION OF RATE FOR PASSENGER TRANSPORTATION BY BUS IN CHERKASY - О. М. Пилипенко; О. О. Огій (Вісник Черкаського державного технологічного університету, 2018)
The method of calculation of the minimum rate for passenger transportation taking into account the interests of transport companies and passengers is given. The calculation has been carried out using the method of economically substantiated costs, which is based on the determination of reason-able value of the price cost of one trip of a passenger, and also takes into account the profitability of the company engaged in passenger transportation. The calculation of a socially-oriented rate on the basis of effective public demand is presented.